Comparative Factors Influencing Patterns of Participation in Cassava Value Chain Activities Amongst Smallholder Processors in Kwara and Kogi State, Nigeria - Eliza Aderonke Adedoyin; David Ahmed Adamu; Isaac Tunde Oyebamiji; Deborah Adedoyin Olabode; Olugbenga Agbana; Chiwendu Vivian Ohaeri (Journal of Agriculture and Rural Development Studies)
Despite the high production of cassava in the two States, studies on processors value chain activities of cassava remain inadequate. This study ascertains comparative factors influencing patterns of participation in cassava value chain activities amongst smallholder processors in Kwara and Kogi States, Nigeria. A Multistage sampling technique was used in selecting a total of 179 and 200 respondents. The study describes the participation patterns in cassava processing of the respondents and to analyze the factor influencing the participation patterns amongst cassava processing in the study area. Results showed the mean age of respondents to be 43 and 42 for both States respectively. The result revealed that 34.1% and 38.0% of the respondents falls within age range of 21-30 years. Out of which 84% and 90% participated frequently in cassava processing in Kwara and Kogi States respectively. Factors influencing pattern of participation were age of respondents, years of experience in processing, frequency of extension visit/training and availability of raw cassava were all statically significant and have direct influence on the patterns of participation in processing activities in the Study areas. The study conclude that socio-economic factors play a key role in participation in cassava processing. The study therefore recommended that more training on best processing practices and ready access to raw cassava is required. Government and stakeholder should create policies that bridge the rareness in participation pattern through supply of processing facilities, ready market and increase in cassava supply, enhance frequent participation is assured and processors’ livelihood were improved.